Magnetostratigrahy of the exposed lava section east of the IRDP drill hole in Reydarfjordur, eastern Iceland (Dataset) ... - Helgason, Johann (Magnetics Information Consortium (MagIC), 2007)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Magnetostratigrahy of the exposed lava section east of the IRDP drill hole in Reydarfjordur, eastern Iceland ...